Effect of Azolla microphylla and Pellets Combination on Meat Quality and Ileal Villi in Muscovy Duck (Cairina moshata) - Rohmah, Anisa; Djunaidi, Irfan H.; Tistiana, Heli (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study aims to evaluate the combination of Azolla microphylla and pellets on meat quality, and ileal villi in muscovy duck (Cairina moshata). The material used was 60 male and female DOD (unsex). The method in this study was an in vivo experiment using a completely randomized design (CRD) with 3 treatments and 5 replicates. The treatment consisted of giving basal feed in the form of pellets and Azolla as much as 0% (P0), 5% (P1), and 10% (P2). The variables measured in this study included meat pH, cooking loss, water holding capacity, tenderness, number of villi, villi length, crypta depth, and villi surface area. The data obtained were then analyzed using Analysis of Variance (ANOVA) and continued with the smallest real difference (BNT). The results showed that the treatment had no significant effect (P>0.05) on meat pH, cooking loss, tenderness, number of villi, villi length, crypta depth, and villi surface area but had a significant effect (P<0.05) on water holding capacity. The addition of Azolla microphylla in the basal feed in the form of pellets to the carcass characteristics of ducks (Cairina moshata) up to 10% level can increase the water holding capacity. Keywords: Azolla, Muscovy Duck, Meat quality, Ileal villi